Internationalization strategies of Thai private higher education: Recruiting and supporting Chinese students - Poedloknimit, Chunipha; Punnanan, Chonnapha (Journal of International Students, 2025)
This study examines the experiences of Chinese students enrolled in Thai private higher education institutions (PHEIs) and investigates the institutional strategies employed to attract and support them. Facing declining domestic enrollment and intensifying competition, Thai PHEIs increasingly view Chinese student recruitment as essential for institutional sustainability. Grounded in push–pull migration theory, intrinsic motivation theory, and the McKinsey 7S framework, this research employs a phenomenological approach to analyze interviews with 25 participants, including students and institutional stakeholders. The findings indicate that academic pressure in China, cultural and linguistic affinity with Thailand, and affordability are key factors influencing students’ decisions. Successful institutions adopt integrated internationalization strategies across curriculum design, admissions processes, staffing, and student support services. This study contributes to the field of international education by highlighting Thailand's rise as a regional education hub beyond the dominant Anglophone model.